Newman, Wesley and the logic of unity: An inductive approach to ecumenism - Morris-Chapman, Daniel J. Pratt (HTS teologiese studies, 2023)
It is a privilege to be invited to contribute to the Festschrift dedicated to Professor Johan Buitendag, Emeritus Dean, Faculty of Theology and Religion at the University of Pretoria, South Africa. While his own work often examined the relationship between theology and natural science, he was also passionate about ecumenism and, in that spirit, the present essay utilised what might be described as an inductive approach to an important ecumenical question, the unity between Methodists and Catholics. Ecumenical dialogue is often undertaken from a theological and dogmatic perspective. This essay took a different approach in that it sought to inductively examine what might be described as the inner logic of two ecclesial systems (Methodist and Catholic). In doing so, it was premised upon an Aristotelian philosophical principle, epistemic fit, in that it presupposed that both these ecclesial bodies possess an intrinsic logic that can be brought to the surface in order to exhibit parallel contours in the wider ecclesial terrain.Contribution: This article fits well within the scope of HTS Teologiese Studies/Theological Studies in that it contributed to a new subdiscipline in epistemology, which explores the conceptual and epistemological dimensions of ecclesiology. Using the concept of epistemic fit, the article offered an inductive approach to some of the practical issues that emerge in ecumenical dialogue.